(untitled) - Patterson, Thomas E.; Thomas E. Patterson (Boston, 2008)
Known for its clear narrative voice, impeccable scholarship, and affordability, Alan Brinkley's The Unfinished Nation offers a concise but comprehensive examination of American History. Balancing social and cultural history with traditional political and diplomatic themes, it tells the story of the diversity and complexity of the United States and the forces that have enabled it to survive and flourish despite division. This fifth edition features eight new essays and enhanced coverage of recent events and developments in the continuing American story
Keywords: Political science; Texas